The stressors of being young and Black: Cardiovascular health and Black young adults. Issue 5 (3rd May 2016) - Lee, Anna K.; Corneille, Maya A.; Hall, Naomi M.; Yancu, Cecile N.; Myers, Micha
Abstract : Objective: To examine the impact of stressors relevant to the lives of Black young adults including racial, financial, occupational, and general stress and psychological distress on cardiovascular disease (CVD) risk. Specifically, this study examined the relationship between multiple psychosocial stressors and two CVD risk indicators (i.e. obesity and blood pressure). Design: This study used a quantitative design which included surveys, the collection of anthropometric and blood pressure (BP) measures. Participants were 124 Black college students aged 18 to 27 years old. Main Outcome Measures: Participants completed measures to assess psychological distress, general, occupational, financial and racial stress. Measures of body mass index (BMI), waist-to-hip ratio (WHR) and BP were collected to assess CVD risk. Results: Findings indicated a significant effect of internalised racism on BMI and a significant effect of individual racial stress on diastolic BP. Also, depression was significantly associated with systolic BP. There were no significant results for WHR. Conclusion: Findings suggested that the relationship among racial stress, psychological distress and CVD be further explored.